PENGARUH LITERASI MANASIK UMRAH DAN PELAYANAN TERHADAP KELANCARAN DAN KEPUASAN JAMA’AH DI PT. DPRIADI BAROKAH UTAMA MATARAM - Mirnasari, Dewi (Mudabbir: Jurnal Manajemen Dakwah, 2022)
This research aims to find out whether there is an influence of literacy and Umrah ritual services on the smoothness and satisfaction of congregational worship at PT. Dpriadi Barokah Utama Mataram. The research method in this research uses a quantitative approach and is a population study with 30 respondents. The data collection technique used in this research uses questionnaires and the data analysis technique in this thesis uses Validity Test, Reliability, Classical Assumption Test, Simple Regression Analysis and Multiple Regression Analysis. Based on the results of multiple linear regression analysis, it is known that there is no positive and significant influence between literacy and Umrah ritual services on the smoothness of congregational worship at PT. Dpriadi Barokah Utama Mataram. This is proven by the results of the f test which simultaneously obtained a calculated f value of 0.28 with a significance level of 0.972. The value of Ftable is 3.34, therefore the value of fcount< ftabel. Meanwhile, the influence of literacy and Umrah ritual services on congregational worship satisfaction with a significance level of 0.005 and an F value of 6.460. The f table value is 3.34. The large influence of literacy and service on congregational worship satisfaction, with the results of a coefficient of determination of 32.4% and 67.6%, is influenced by other factors not examined in this research.